Insulin Autoimmune Syndrome: A Systematic Review - MingXu Lin; YuHua Chen; Jie Ning (International Journal of Endocrinology)
Insulin autoimmune syndrome (IAS) is a rare endocrine disorder characterized by recurrent episodes of severe hypoglycemia, markedly elevated serum insulin, and positive insulin autoantibodies. In recent years, various countries have reported it one after another. It can be seen that we must pay attention to this disease. The diagnosis of IAS is challenging, requiring a careful workup aimed at excluding other causes of hyperinsulinemic hypoglycemia. High levels of insulin autoantibodies are found in patients, and C-peptide is not parallel to insulin, which could be diagnostic. IAS is a self-limiting disease with a good prognosis. Its treatment mainly includes symptomatic supportive treatment, such as adjusting the diet and using acarbose and other drugs to delay the absorption of glucose to prevent hypoglycemia. For patients with severe symptoms, available treatments may include drugs that reduce pancreatic insulin secretion (such as somatostatin and diazoxide), immunosuppressants (glucocorticoids, zaprin, and rituximab), and even plasma exchange to remove autoantibodies from the body. This review provides a comprehensive analysis of the epidemiology, pathogenesis, clinical manifestations, diagnosis and identification, and monitoring and treatment management of IAS.